The Influence of Perceived Ease of Use and Perceived Usefulness on The Continuance Intention of Kopra by Mandiri which is Mediated by The Trust in The Tapal Kuda Area - Amin Amin; Ika Barokah Suryaningsih; Sri Wahyu Lelly Hana Setyanti (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This research aimed to determine the influenced of perceived ease of use and perceived usefulness on continuance intention of Kopra by Mandiri which is mediated by trust in the Tapal Kuda area. This research used the Explanatory Research type. Researchers used the proportional random sampling method or random sampling. The author used the determination of the sample size in this research based on the Slovin method as a measuring tool for calculating sample size so that research could be made easier. The number of research samples determined using the Slovin formula was 321 people. The data analysis method used Structural Equation Modeling (SEM) with the SmaprtPLS application. The results of the research showed that Perceived Ease of Use influenced Trust Kopra by Mandiri in the Tapal Kuda area. Perceived Usefulness influenced Trust Kopra by Mandiri in the Tapal Kuda area. Perceived Ease of Use influenced Continuance Intention of Kopra by Mandiri in the Tapal Kuda area. Perceived Usefulness influenced Continuance Intention of Kopra by Mandiri in the Tapal Kuda area. Trust influenced the Continuance Intention of Kopra by Mandiri in the Tapal Kuda area. Trust mediated the influence of Perceived Ease of Use on Continuance Intention of Kopra by Mandiri in the Tapal Kuda area. Trust mediated the influence of Perceived Usefulness on Continuance Intention of Kopra by Mandiri in the Tapal Kuda area.